Implementasi Total Quality Management (TQM) di MAN 1 Bungo - Atika, Atika (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This research aims to analyze the implementation of Total Quality Management (TQM) at MAN 1 Bungo, Jambi Province, as an effort to improve the quality of education. The research approach used is qualitative with a case study design. Data was obtained through in-depth interviews with the head of the madrasah, teachers, and administrative staff; observation of quality management activities; as well as document analysis. The results of the study show that MAN 1 Bungo has implemented TQM principles such as strategic quality planning, involvement of all madrasah members, and continuous evaluation. The main supporting factors are the visionary leadership of the head of the madrasah, teacher commitment, and community participation. The obstacles found include budget limitations, resistance from some teachers to innovation, and lack of quality management training. This study recommends strengthening the internal quality assurance system, ongoing training, and awarding outstanding teachers.